Use of Machine Learning to predict patient developing a disease or condition for early diagnose - Moazzam Siddiq (International Journal of Multidisciplinary Sciences and Arts, 2022)
Machine learning algorithms have shown promise in predicting the likelihood of a patient developing a disease or condition. Early diagnosis of diseases such as cancer, diabetes, and cardiovascular diseases can improve the patient's outcomes and quality of life. In this paper, we review the current state of machine learning algorithms for disease prediction and discuss their potential applications in clinical practice. We start by discussing the types of data used for disease prediction, including clinical data, genetic data, and imaging data. We then review the different types of machine learning algorithms used for disease prediction, including logistic regression, decision trees, random forests, and deep learning. We discuss the advantages and limitations of each algorithm and provide examples of their applications in disease prediction. Next, we discuss the challenges associated with implementing machine learning algorithms in clinical practice, such as data privacy concerns and the need for high-quality data. We also discuss the ethical considerations associated with the use of machine learning algorithms for disease prediction. Finally, we highlight the potential benefits of using machine learning algorithms for disease prediction, including improved patient outcomes, reduced healthcare costs, and personalized medicine. We conclude that machine learning algorithms have the potential to revolutionize disease prediction and early diagnosis, but further research is needed to address the challenges associated with their implementation in clinical practice.